The Challenges of Learning Social Science in the "Merdeka" Curriculum in Elementary Schools - Anggi Amalia Fannisa; Devina Anggraini; Karina Novita Romdani; Monica Tiara Dewi (MANDALIKA : Journal of Social Science, 2023)
The "Merdeka" curriculum is an educational approach that aims to pay attention to individual needs and encourage independence in learning. In the social studies learning context, Their Curriculum recognizes the importance of developing a comprehensive understanding of social, political, and economic issues that affect everyday life. Social science learning covers various aspects such as history, geography, economics, politics, and sociology. The challenge faced in social studies learning is to ensure that students understand the complexities and relationships between various concepts and phenomena in social studies. Students also need to learn about analytical and problem-solving skills that are relevant in social contexts. Another challenge is facing technological developments and globalization which can affect the way students obtain information and interact with the outside world. Social science learning needs to consider the integration of technology in the learning process to ensure students can understand and deal with social changes that occur. In addition, it is also important to ensure that social studies learning includes different perspectives and social experiences. In an increasingly heterogeneous society, students need to understand and appreciate the diversity of cultures, values ​​and social systems that surround them. In facing this challenge, an active, collaborative, and problem-based learning approach can be an effective solution. Through this approach, students can engage in discussions, research, and real projects that are relevant to their daily lives. This will help them develop the deep understanding and skills needed to participate actively in society. In conclusion, Social Studies learning under the "Merdeka" Curriculum approach faces challenges in understanding the complexity of social issues, integrating technology, respecting diversity, and developing relevant skills. However, with an appropriate learning approach, students can overcome these challenges and become socially skilled and informed individuals.